2022
DOI: 10.1186/s12951-022-01682-5
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic mediated multifunctional tumor antigen trapping nanoparticles inhibit the recurrence and metastasis of ovarian cancer by enhancing tumor immunogenicity

Abstract: The hypoimmunogenicity of tumors is one of the main bottlenecks of cancer immunotherapy. Enhancing tumor immunogenicity can improve the efficacy of tumor immunotherapy by increasing antigen exposure and presentation, and establishing an inflammatory microenvironment. Here, a multifunctional antigen trapping nanoparticle with indocyanine green (ICG), aluminum hydroxide (Al(OH)3) and oxaliplatin (OXA) (PPIAO) has been developed for tumor photoacoustic/ultrasound dual-modality imaging and therapy. The combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Employing MIA-PaCa-2-treated cells, the Ce6-R-Exo group's PA signal was 9.0 and 5.5 times higher than the controls as well as Ce6liposome groups, suggesting that compared to liposomal administration distribution of Ce6 through exosomes to tumor cells was much more significant, leading to a stronger PA signal for management of pancreatic cancer. 24 Zhong et al 25 developed a multipurpose antigen-caging nanoparticle made of poly(lactic-co-glycolic acid) and oxygencarrying perfluoropentane (PFP) loaded with ICG, aluminum hydroxide (Al(OH) 3 ), an adjuvant approved by the FDA, and oxaliplatin (PPIAO) to increase antigen presentation and to set up an inflammatory microenvironment. The PPIAO-phagocytosis rate of ID8 mouse ovarian tumor cells was 96.3%, and there was a rise in intracellular ROS owing to oxygen-carrying PFP after 808 nm laser and ultrasonic irradiation, which also triggered the total apoptotic cell death of 95.71%.…”
Section: Combined Photoimmunotheranostic Nanomedicinesmentioning
confidence: 99%
See 3 more Smart Citations
“…Employing MIA-PaCa-2-treated cells, the Ce6-R-Exo group's PA signal was 9.0 and 5.5 times higher than the controls as well as Ce6liposome groups, suggesting that compared to liposomal administration distribution of Ce6 through exosomes to tumor cells was much more significant, leading to a stronger PA signal for management of pancreatic cancer. 24 Zhong et al 25 developed a multipurpose antigen-caging nanoparticle made of poly(lactic-co-glycolic acid) and oxygencarrying perfluoropentane (PFP) loaded with ICG, aluminum hydroxide (Al(OH) 3 ), an adjuvant approved by the FDA, and oxaliplatin (PPIAO) to increase antigen presentation and to set up an inflammatory microenvironment. The PPIAO-phagocytosis rate of ID8 mouse ovarian tumor cells was 96.3%, and there was a rise in intracellular ROS owing to oxygen-carrying PFP after 808 nm laser and ultrasonic irradiation, which also triggered the total apoptotic cell death of 95.71%.…”
Section: Combined Photoimmunotheranostic Nanomedicinesmentioning
confidence: 99%
“…In an ovarian tumor model, a PA-mediated PPIAO NP combined treatment increased tumor the temperature (55 °C during the treatment by thermal infrared imaging), which encouraged greater CD8+ T cell stimulation in vivo and effectively reduced primary (65%) and metastatic (50%) tumor development. 25 As an example of immunostimulation through ICD, Chen et al 26 reported a PEGylated antimony (Sb) nanopolyhedron system using a typical group VA semimetal antimony, for plasmonic PTT. An effective ligand-guided growth approach for manufacturing Sb nanopolyhedrons (Sb NPHs) with high photothermal conversion efficiency, great biocompatibility, and PTT durability was used.…”
Section: Combined Photoimmunotheranostic Nanomedicinesmentioning
confidence: 99%
See 2 more Smart Citations
“…There have also been reports of other types of non-PEGylated ACNPs, such as those made of natural polysaccharides (Guibin Pang et al, 2019). PEGylated PLGA NPs loaded with Al(OH) 3 nanoclusters (NCs) have also been explored as ACNPs (Zhong et al, 2022). Al(OH) 3 NCs capture antigens via electrostatic, hydrophobic as well as metal-ligand exchange interactions.…”
Section: Increasing Antigen Presentationmentioning
confidence: 99%